2020
DOI: 10.3390/ijms21197216
|View full text |Cite
|
Sign up to set email alerts
|

NRF2 and PPAR-γ Pathways in Oligodendrocyte Progenitors: Focus on ROS Protection, Mitochondrial Biogenesis and Promotion of Cell Differentiation

Abstract: An adequate protection from oxidative and inflammatory reactions, together with the promotion of oligodendrocyte progenitor (OP) differentiation, is needed to recover from myelin damage in demyelinating diseases. Mitochondria are targets of inflammatory and oxidative insults and are essential in oligodendrocyte differentiation. It is known that nuclear factor-erythroid 2-related factor/antioxidant responsive element (NRF2/ARE) and peroxisome proliferator-activated receptor gamma/PPAR-γ response element (PPAR-γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 60 publications
(104 reference statements)
2
17
0
Order By: Relevance
“…PPARγ can regulate the transcription of target genes, inhibit the activation of immune cells and the expression of inflammatory factors, thus alleviating airway inflammation [ 40 ]. Recently, a large number of studies have shown that PPARγ has important antioxidant protection [ 41 ]. In addition, PPARγ activation can directly inhibit the production of ROS and promote the expression of antioxidant genes such as GST and SOD, thus antagonizing antioxidant stress [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…PPARγ can regulate the transcription of target genes, inhibit the activation of immune cells and the expression of inflammatory factors, thus alleviating airway inflammation [ 40 ]. Recently, a large number of studies have shown that PPARγ has important antioxidant protection [ 41 ]. In addition, PPARγ activation can directly inhibit the production of ROS and promote the expression of antioxidant genes such as GST and SOD, thus antagonizing antioxidant stress [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor erythroid-2-related factor 2 (Nrf2) is involved in the maintenance of cellular redox homeostasis through the up-regulation of antioxidant enzymes. Different studies suggest that Nrf2 is an effective modulator of stem cell self-renewal and differentiation [ 32 , 33 , 34 ]. Apurinic/apyrimidinic endonuclease 1 (APE1), also called Redox Factor-1 [ 1 ], is a pleiotropic protein that regulates various cellular functions including oxidative stress and has a role in the maintenance of the stem cell pool and differentiation by modulating intracellular redox homeostasis [ 35 , 36 , 37 ].…”
Section: Noxs and Ros: Effectors And Modulators Of Redox And Metabolic Homeostasis In Stem Cellsmentioning
confidence: 99%
“…Pioglitazone has been shown to inhibit, significantly for all, albeit moderately for some, the decrease in total thiol, SOD and catalase levels and the increase in malondialdehyde (MDA, a marker of PUFA peroxidation) levels in hippocampal and cortical extracts, in a rat model of hypothyroidism, a phenotype known to cause neurological damage [48]. Pioglitazone has also been shown to induce expression of TFAM and PGC-1α along with increased mitochondrial biogenesis and to restore mitochondrial membrane potential after challenge with rotenone, an inhibitor of the mitochondrial transport chain complex 1, in rat oligodendrocyte cultures [49]. Recent reports also documented a similar role of PPARγ and agonists in non brain tissues or cells.…”
Section: Energy Supply Oxidative Stress and Mitochondriamentioning
confidence: 99%
“…A wealth of studies recently reviewed in [69] showed that PPARγ supports NSC growth, survival and stemness maintenance and positively regulates neuronogenesis and neurite outgrowth in maturing neurons. More recently, pioglitazone was shown to promote differentiation of rat primary oligodendrocytes [49].…”
Section: Neurogenesismentioning
confidence: 99%